THE TRANSFORMATIVE ROLE OF INTERNATIONAL ACTORS IN THE DEVELOPMENT OF THE SOCIAL AND SOLIDARITY ECONOMY POLICY IN THE REPUBLIC OF SERBIA - СТОЈАНОВИЋ, Тамара Г.; Mihajlović, Suzana (Serbian political thought, 2025)
In the last few decades, in the field of public policy creation, particularly economic and social policies, the political learning approach has been recognized as a way to ensure the efficient and effective transfer of policies between countries. International actors play a key role in this process, with their methods of engagement ranging from providing comparative data analysis on a global scale in specific areas to offering expert and financial assistance in the capacity building of actors reforming national policies. The economic and social consequences of international crises in recent years provide an additional impetus for reforms in the areas of the labor market and poverty reduction. Alongside the need to improve active labor market programs, increasingly frequent initiatives recommend the development of the social and solidarity economy as a possible response to the social exclusion of vulnerable groups. Considering the previously stated, the objectives of the paper are to identify key international actors in the development of the concept of social and solidarity economy within global frameworks, to analyze their programs and initiatives, and to examine the actions of international actors in the development of social and solidarity economy in the national context of the Republic of Serbia. Based on the content analysis of documents relevant to the international actor’s actions in this field, the paper presents several conclusions. The engagement of international actors was significant in the activities promoting social and solidarity economy, furthermore in operationalizing the concept, defining its key characteristics and principles, providing expert and financial support for the sector development, as well as offering platforms for the exchange of best practices among countries and local communities. The International Labour Organization (ILO), the Organization for Economic Co-operation and Development (OECD), the United Nations (UN), and the European Union (EU) have been identified as particularly significant international actors in this field. Within the national framework of the Republic of Serbia, the development of social and solidarity economy, accompanied by the development of social entrepreneurship, in relation to the engagement of international actors, can be divided into two phases with specific characteristics. In the first phase of conceptualizing reforms towards building an ecosystem conducive to social and solidarity economy, the leading impact was made by the European Union in cooperation with governmental and non-governmental actors, through the promotion of social entrepreneurship, the development of the concept, and the approach to be applied in public policies. Simultaneously, the European Union funded concrete activities for the development of social entrepreneurship in practice. In the second phase, the phase of institutionalizing social entrepreneurship, international development agencies from European states took on a more significant role, with occasional engagement from the United Nations, in building the capacities of national actors towards achieving efficient operations of entities that belong to the social and solidarity sector in the Republic of Serbia.